326 Sleep Stages Variation in Intracranial Pressure and Pulse Amplitude. (April 2023) - Darie, Lucia; Bancroft, Matthew; Glorioso, Dolora; Pandit, Anand; Moncur, Eleanor; Thorne, Lewis; Radcliffe, Jeremy; Eriksson, Sofia; Watkins, Laurence Dale; Toma, Ahmed
Abstract : INTRODUCTION: It is thought that CSF pulsatility has an important role in brain physiology during sleep. Yet few studies have looked into changes of ICP and pulsatility during sleep. METHODS: A single centre prospective cohort study. Patients undergoing 24 h ICP monitoring for suspected CSF dynamic disorders underwent concomitant polysomnography. Clinical and radiological presentation were derived from the patient's records. Aggregate mean ICP and pulse amplitude (mPA) values were recorded for each sleep stage. Sleep staging was performed in conformity with the AASM guidelines. Within subject values were compared using repeated-measures, one-way ANOVA. Post-hoc paired t-tests were used to compare sleep stages between groups corrected for multiple comparisons (Benjamini-Hochberg method). RESULTS: A total of 12 patients (10 females, 2 males; mean age 40.8 years, SD+/- 12.9) with complete data were analysed. There were significant differences in mean ICP between sleep stages (F(3, 33) = 10.7, p < 0.00001). Post-hoc paired t-tests revealed significant differences between rapid eye movement (REM; mean ICP 14.4 mmHg) and all other sleep stages (mean ICP/N1 = 12.0 mmHg, t = -3.6, p = 0.004; ICP/N2 = 11.8 mmHg, t = -4.3, p = 0.001; ICP/N3 = 12.3 mmHg, t = -3.5, p = 0.004). Significant differences were also found in mPA between sleep stages (F(3, 33) = 5.7, p = 0.003) confirmed on post-hoc paired t-tests: REM (mean mPA 5.5 mmHg and all other sleep stages: mPA/N1 = 4.7 mmHg, t = -2.3, p = 0.04; mPA/N2 = 4.3 mmHg, t = -2.7, p = 0.02; mPA/N3 = 4.5 mmHg, t = -2.3, p = 0.04). CONCLUSIONS: REM is characterized by higher ICP and mPA values, result confirmed in near-normal patients included in this cohort.